Selective Androgen Receptor Modulators Combined with Treadmill Exercise Have No Bone Benefit in Healthy Adult Rats - Marina Komrakova; Arndt Friedrich Schilling; Wolfgang Lehmann; Veselin Vasilev; Katerina Georgieva; Fanka Gerginska; Nikolay Boyadjiev; Slavi Delchev (MDPI AG, 2023)
The effects of combination treatments using the selective androgen receptor modulators (SARMs) ostarine (OST) or ligandrol (LIG) with treadmill exercise (TE) were studied in healthy adult rats. Fifteen-week-old male Wistar rats were divided into groups (n = 10/group). Experiment 1 consisted of (1) Control group: sedentary rats receiving vehicle; (2) OST: sedentary rats receiving OST; (3) TE: training rats receiving vehicle; (4) OST + TE: training rats receiving OST. Experiment 2 consisted of (1) LIG: sedentary group receiving LIG; (2) LIG + TE: training group receiving LIG. The TE regime was as follows: 25 m/min, 5° elevation, 40 min, five times/week, and the sedentary regime was 5 min, three times/week. OST and LIG were administered subcutaneously (0.4 mg/kg body weight/day, five times/week). After eight weeks, bone samples underwent microcomputed tomographical, biomechanical, histological, and ashing analyses. All the treatments had weak effects on the bone structure without affecting bone biomechanics. The OST + TE improved bone structure, while the LIG + TE had unfavorable effects. In serum, OST, OST + TE, and LIG + TE altered cholesterol and lipoprotein levels; TE did not change the serum parameters. The SARM treatments had no clear bone benefit, and the serum effects can be considered as side effects. TE represents a safe treatment. Because SARMs are increasingly applied in gyms along with physical activities, attention should be paid to possible side effects.